2017
DOI: 10.5194/bg-14-4577-2017
|View full text |Cite
|
Sign up to set email alerts
|

Coccolithophore fluxes in the open tropical North Atlantic: influence of thermocline depth, Amazon water, and Saharan dust

Abstract: Abstract. Coccolithophores are calcifying phytoplankton and major contributors to both the organic and inorganic oceanic carbon pumps. Their export fluxes, species composition, and seasonal patterns were determined in two sediment trap moorings (M4 at 12 • N, 49 • W and M2 at 14 • N, 37 • W) collecting settling particles synchronously from October 2012 to November 2013 at 1200 m of water depth in the open equatorial North Atlantic.The two trap locations showed a similar seasonal pattern in total coccolith expo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 94 publications
(145 reference statements)
6
68
0
Order By: Relevance
“…In this ecosystem, several long-term continuous sediment-trap-based monitoring records are available since the late 1980s. Until now, stud-ies monitoring variability of this seasonally dynamic ecosystem mostly focused on the variability of bulk fluxes (Fischer et al, 1996(Fischer et al, , 2016(Fischer et al, , 2019Bory et al, 2001;Marcello et al, 2011;Skonieczny et al, 2013), particular groups of microorganisms (Lange et al, 1998;Romero et al, 1999Romero et al, , 2002Romero et al, , 2003Köbrich and Baumann, 2008;Romero and Armand, 2010;Zonneveld et al, 2010;Köbrich et al, 2016;Romero and Fischer, 2017;Guerreiro et al, 2019) or seasurface temperature (Müller and Fischer, 2001;Mollenhauer et al, 2015). However, the simultaneous comparison of the seasonal and interannual dynamics of several phyto-and zooplankton communities by means of multiyear sediment trap experiments has not been performed in this region and is rare in other EBUEs or other ocean areas as well (Bringué et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this ecosystem, several long-term continuous sediment-trap-based monitoring records are available since the late 1980s. Until now, stud-ies monitoring variability of this seasonally dynamic ecosystem mostly focused on the variability of bulk fluxes (Fischer et al, 1996(Fischer et al, , 2016(Fischer et al, , 2019Bory et al, 2001;Marcello et al, 2011;Skonieczny et al, 2013), particular groups of microorganisms (Lange et al, 1998;Romero et al, 1999Romero et al, , 2002Romero et al, , 2003Köbrich and Baumann, 2008;Romero and Armand, 2010;Zonneveld et al, 2010;Köbrich et al, 2016;Romero and Fischer, 2017;Guerreiro et al, 2019) or seasurface temperature (Müller and Fischer, 2001;Mollenhauer et al, 2015). However, the simultaneous comparison of the seasonal and interannual dynamics of several phyto-and zooplankton communities by means of multiyear sediment trap experiments has not been performed in this region and is rare in other EBUEs or other ocean areas as well (Bringué et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…During this period, the relative abundance of F. profunda may have been as low as 20% in the western Pacific (Jin et al, ), and the primary productivity may have been as large as 161–237 gC·m −2 year −1 , based on the transfer functions in the equatorial Indian Ocean and SCS (Beaufort et al, ; Zhang et al, ) being approximately 50–120% higher than the oligotrophic modern western Pacific. Such a high phytoplankton productivity required a large quantity of nutrient inventory at the ocean's surface, which may have been fueled by a long‐term enhanced aeolian dust deposition (Guerreiro et al, ), weathering (Rickaby et al, ), terrestrial inputs (Flores et al, ), and a shallowing of the thermocline (mixed layer depth) and nutricline. However, no such evidence was reported to support these ideas from a global perspective or at least in the western Pacific.…”
Section: Discussionmentioning
confidence: 99%
“…Bonnet et al (2005) and Blain et al (2004) showed that Saharan dust from the Hoggar regions in southern Algeria is a 25 potential source of bioavailable Fe that stimulates mainly the picophytoplankton (< 2 µm) in the Mediterranean Sea and diatoms in the northeast Atlantic Ocean. Observed under natural conditions, Guerreiro et al (2017) reported a flux increase of opportunistic coccolithophore species during the fall 2013 in the western tropical North Atlantic in combination with a wet dust deposition event, suggesting that calcifying phytoplankton also benefited from Saharan dust-born nutrients in this region.…”
Section: Variations Related To Different Types Of Dust 10mentioning
confidence: 97%
“…Saharan dust deposition has been shown to have a great impact in the biogeochemical cycling of oceanic waters underneath the most prominent dust plumes blown towards the Mediterranean Sea (Bonnet et al, 2005;Romero et al, 2011;Desboeufs et al, 2014;Guieu et al, 2014a;Ridame et al, 2014) and towards the tropical North Atlantic Ocean (Jickells, 1999;Baker et al, 2003;Mills et al, 2004;Bristow et al, 2010). Both fertilization (Jickells et al, 2005;Pabortsava et al, 2017;Guerreiro et al, 2017) and ballasting of marine snow aggregates (Van der Jagt 10 et al, 2018) from dust deposition impact the carbon dioxide content of surface waters. Mesocosm experiments in the Mediterranean Sea revealed that dust predominates the particulate phase that is exported to the base of the mesocosms (Desboeufs et al, 2014) and that up to 50 % of the particulate organic carbon flux (POC) can be associated with lithogenic dust particles (Bressac et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation